A Sentiment Analysis on Pesantren Entrepreneurship - Syahdatul Maulida (SMART Insight, 2022)
This study aims to look at the development of public sentiment towards pesantren entrepreneurship. This study uses the sentiment analysis method with the help of SentiStrength software. The type of data used is secondary data derived from indexed scientific publications database Dimensions. Found as many as 100 scientific publications related to research topics. Then the results show that positive sentiment prevailed with a percentage of 52%, followed by neutral sentiment of 31% and negative sentiment of 17%. 2021 is the year with the highest number of sentiments which are dominated by positive sentiment as many as 13 scientific publications. According to the findings, the majority of people agree with the existence of pesantren entrepreneurship. As a result, an increase in the number of scientific publications on pesantren entrepreneurship in indexed journals is necessary to maintain this favorable view.